THE CURRENT STATE OF ARTIFICIAL REEFS IN LEBAH COASTAL WATERS, KARANGASEM, BALI: AN EVALUATION ON THE COASTAL RESOURCE REHABILITATION PROJECT - Isa Nagib Edrus; Suprapto Suprapto (Indonesian Fisheries Research Journal, 2005)
The study was conducted in May 2001 wlth aims to identifl and examine changes the biotic condition of coastal resources. The study used dual approaches of old and new data collections followed by statistical test of Wilcoxon Rank Sum Test.